Counseling for Young People and Families Affected by Child Sexual Exploitation and Abuse: A Qualitative Investigation of the Perspective of Young People, Parents, and Professionals. Issue 1 (2nd January 2021) - Farr, Joanna; Edbrooke-Childs, Julian; Town, Rosa; Pietkiewicz, Deborah; Young, Ian; Stapley, Emily
ABSTRACT: Despite growing awareness of the negative impact of child sexual exploitation on young people's psychological, emotional and relational lives, little is known about how counseling can support young people and their families. The aim of this study was to explore the experience of counseling for young people and parents affected by child sexual exploitation and abuse, with a view to examining what facilitates progress, from the perspective of young people, parents and professionals. In-depth semi-structured interviews were conducted with 10 young people, 8 parents and 7 professionals and were analyzed using thematic analysis. Findings suggest that through counseling, young people experienced affective and relational improvements that were attributed to the process. Characteristics of the counseling relationship that facilitated progress included being able to talk openly in a caring, non-judgmental and unpressurized environment, as well as receiving advice, techniques or solutions within a holistic approach. Facets of service delivery were also highlighted, including the provision of confidentiality, flexibility and consistency, along with a multi-agency approach that promoted engagement. Perceived obstacles to progress included resistance at the outset and service location issues.